A first look at the Gargano (southern Italy) seismicity as seen by the local scale OTRIONS seismic network - Salvatore de Lorenzo; Annalisa Romeo; Luigi Falco; Maddalena Michele; Andrea Tallarico (Annals of Geophysics, 2014)
On April 2013, a local scale seismic network, named OTRIONS, composed of twelve short period (1 Hz) three component seismometers, has been located in the northern part of the Apulia (southern Italy). In the first two months of data acquisition, the network recorded about one hundred very small (ML<2) magnitude earthquakes. A three-layer 1D VP velocity model was preliminarily computed, using the recordings of earthquakes occurred in the area in the period 2006-2012 and recorded by the national seismic network of INGV (Istituto Nazionale di Geofisica e Vulcanologia). This model was calibrated by means of a multi-scale approach, based on a global search of the minimum misfit between observed and theoretical travel times. At each step of the inversion, a grid-search technique was implemented to infer the elastic properties of the layers, by using HYPO71 to compute the forward models. In a further step, we used P and S travel times of both INGV and OTRIONS events to infer a minimum 1D VP velocity model, using a classical linearized inversion approach. Owing to the relatively small number of data and poor coverage of the area, in the inversion procedure, the VP/VS ratio was fixed to 1.82, as inferred from a modified Wadati diagram. The final 1D velocity model was obtained by averaging the inversion results arising from nine different initial velocity models. The inferred VP velocity model shows a gradual increase of P wave velocity with increasing the depth. The model is well constrained by data until to a depth of about 25-30 km.